Analisis Tingkat Kepuasan Konsumen Terhadap Kualitas Produk Kopi Warbon di “Warbon Cafe” Bekasi Dengan Menggunakan Metode Quality Function Deployment (QFD) - Ignashia, Maria Cory; Yuarini, Dewa Ayu Anom; Hartiati, Amna (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
In January-May 2023, Warbon Cafe experienced a 23% decrease in sales. This was due to the emergence of competitors around Warbon Café that also sell similar products. The purpose of this study is to determine the attributes of Warbon Coffee considered important by consumers, analyze the importance and satisfaction levels regarding Warbon Coffee products, and determine improvement strategies to enhance the quality of Warbon Coffee products. This research employs the Quality Function Deployment (QFD) method. The results of this study show that there are 7 consumer importance attributes with the highest importance values being presentation (4.38), taste (4.32), price (4.16), volume (4.18), physical appearance (4.18), aroma (4.01), and the lowest being color (3.9), Furthermore, attributes with the highest satisfaction values are presentation (4.37), taste (4.12), price (4.09); physical appearance (4.02), volume (3.98), color (3.99), and the lowest being aroma (3.94). The strategy to improve product quality prioritizes improvement in aroma, volume, and color attributes, as well as technical parameter improvements in equipment and ingredient preparation, raw material mixing, extraction, and presentation.